Estudio retrospectivo de la atención de enfermería en paciente con embarazo gemelar prematuro - Ferrin Sagnay, José Alejandro (2024)
In a twin pregnancy, more than one fetus develops as a result of the fertilization of two or more eggs or when one egg divides, and those born before 37 weeks of gestation are considered premature. This retrospective study focuses on nursing care in patients with premature twin pregnancy, addressing genetic, obstetric and care aspects related to the comprehensive care of these patients. Prematurity in twin pregnancies is analyzed, highlighting the fundamental role of nursing in the early detection of complications and the promotion of maternal and neonatal health. Genetic aspects are examined, such as the formation of monozygotic and dizygotic twins, as well as the relevance of vaginal progesterone in the prevention of premature birth. In addition, neurodevelopmental morbidity in surviving twins after fetal death of the co-twin and obstetric complications in twin pregnancies are discussed. A nursing care plan adapted to the individual needs of each patient is proposed to guarantee a healthy and safe pregnancy. This study seeks to understand and improve the care provided to patients with premature twin pregnancy from multiple perspectives.